Enlarged hyperechogenic substantia nigra as a risk marker for Parkinson's disease. Issue 2 (31st October 2012) - Berg, Daniela; Behnke, Stefanie; Seppi, Klaus; Godau, Jana; Lerche, Stefanie; Mahlknecht, Philipp; Liepelt‐Scarfone, Inga; Pausch, Christoph; Schneider, Niko; Gaenslen, Alexandra; Brockmann, Kathrin; Srulijes, Karin; et al.
<x xml:space="preserve">Abstract</x> Background SN hyperechogenicity (SN+), determined by transcranial sonography, has been proposed as a risk factor for Parkinson's disease (PD). Recently, we reported a 17.4‐fold increased risk for PD in individuals with SN+ older than 50 years within 3 years. Methods This is the second follow‐up of a prospective, longitudinal, three‐center observational study after 5 years. Of the initial 1, 847 at baseline PD‐free participants 50 years or older, 1, 271 underwent the 5‐year reassessment. Results Within 5 years, 21 individuals developed incident PD. Participants with SN+ at baseline had a more than 20.6 times increased risk to develop PD in this time span than those without this echo feature. Conclusion We thus confirm our finding of the 3‐year follow‐up examination in a longer observation time and higher number of individuals with incident PD and suggest SN+ as an important risk marker for PD. © 2012 Movement Disorder Society